1968
DOI: 10.1172/jci105847
|View full text |Cite
|
Sign up to set email alerts
|

In vitro stimulation by long-acting thyroid stimulator of thyroid glucose oxidation and 32P incorporation into phospholipids

Abstract: AB s T R A C T Long-acting thyroid stimulator (LATS) increased glucose oxidation and 32P incorporation into phospholipids in in vitro experiments with dog thyroid slices. The time course of the response was different from that obtained with thyroid-stimulating hormone (TSH), but was very similar to the delayed effect observed in vivo. During a 45 min incubation, TSH, but not LATS increased glucose oxidation, whereas in longer experiments up to 6 hr, both substances augmented 14CO2 production. Amounts of pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Kriss reported that LATS sometimes increased glucose oxidation in dog liver and spleen slices, but the results were not as consistent as when thyroid slices were used (10). It has also been reported that LATS stimulates lipolysis in adipose tissue, an effect similar to that of TSH (26).…”
Section: Discussionmentioning
confidence: 92%
“…Kriss reported that LATS sometimes increased glucose oxidation in dog liver and spleen slices, but the results were not as consistent as when thyroid slices were used (10). It has also been reported that LATS stimulates lipolysis in adipose tissue, an effect similar to that of TSH (26).…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, biochemical studies have shown that LATS stimulates glucose oxidation (Scott et Shishiba et al, 1970) and increases both the uptake of 32P into phospholipid and RNA synthesis (Field, 1968;Ochi and DeGroot, 1968).…”
Section: Mode Of Action Of Latsmentioning
confidence: 93%
“…The prototype of organotypic tissue slice culture was developed by Dr. Harford and coworkers in the 1950s 28 . This technique was initially utilized for the assessment of pharmacological efficacy around 1970 29 , 30 . The expediting evolvement of immunotherapy facilitates the application of this technique to evaluate the immune checkpoint blockade, and adoptive cellular therapy response on tumors in recent years 31 , 32 ( Figure 1 ).…”
Section: Organotypic Tissue Slice Culturesmentioning
confidence: 99%